Using defamilisation typologies to study the Confucian welfare regime. Issue 1 (February 2015) - Yu, Sam; Chau, C.M.; Lee, K.M.
Abstract : Since Esping-Andersen classified the 18 Organization for Economic Co-operation and Development (OECD) countries into the "three worlds of welfare capitalism" in 1990, the comparative studies of welfare have been dominated by the responses to this study. This paper focuses on two of these responses. The first response is concerned with the gender insensitivity of Esping-Andersen's way of categorizing the welfare regimes. The second response is concerned with the issue that the East Asian countries are under-represented in the 18 OECD countries. To make contributions to these responses, two analytical tasks are conducted. First, we build new defamilisation typologies covering both East Asian countries and OECD countries. Second, we demonstrate that the evidence generated from the typologies suggest that some of the indispensable conditions for the development of a Confucian welfare regime do not exist.